Effects Of Psidium Guajava Crude Leaf Methanol-Extract On Lowering Blood Sugar Levels In Rat - Belgis Belgis (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Blood sugar levels, or blood glucose levels, are crucial for overall health and are regulated by the pancreas through insulin. Normal blood sugar levels range between 70-99 mg/dL when fasting and up to 140 mg/dL two hours after eating. Abnormal blood sugar levels can suggest a variety of health issues, including hypoglycemia (low blood sugar levels caused by excess insulin, certain drugs, or illnesses such as diabetes) and hyperglycemia (high blood sugar levels associated with diabetes). Regular blood sugar monitoring is necessary, especially for diabetics. Guava, a tropical fruit, includes a variety of phytochemicals that have been linked to pharmacological benefits such as antibacterial capabilities. This research uses an extraction process involving solid-liquid extraction or maceration, with methanol being the optimal solvent. The extract yields 9.51%. Wistar rats are used to investigate its antidiabetic efficacy. The rats are divided into three groups: positive control, negative control, and extract treatment. Diabetes is induced by subcutaneous injection of Alloxan, followed by oral administration of the methanol extract. Blood glucose levels are assessed after fasting for 6-8 hours. The extract from dried Guava leaf powder yields a concentrated extract with a 9.51% yield. In vivo assessments showed a significant reduction in blood glucose levels in rats treated with guava leaf extract, suggesting potential anti-hyperglycemic effects. The phenolic compounds in guava leaves contribute to antioxidant and anti-hyperglycemic effects. The study highlights the potential therapeutic effects of guava mint leaves and their extract components for diabetes management and antioxidant health benefits.